2017
DOI: 10.1093/cid/cix001
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Invasive Candidiasis in Extremely Low Birth Weight Infants: Perinatal Acquisition Predicts Poor Outcome

Abstract: ELBW infants with EOD have a very poor prognosis compared to those with LOD. The role of perinatal transmission in EOD is supported by its association with chorioamnionitis, vaginal delivery, and pneumonia. Dissemination and cardiovascular involvement are common, and affected infants often die. Empiric treatment should be considered for ELBW infants delivered vaginally who have pneumonia and whose mothers have chorioamnionitis or an intrauterine foreign body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Therefore, prevention of neonatal sepsis in infants born very preterm (<32 weeks' gestation) is clearly desirable as this would contribute to reducing mortality and morbidity (22,59). There is ample evidence indicating that neonatal sepsis can lead to long-term disability, including cerebral palsy, cognitive deficit, delayed mental and psychomotor, vision and hearing impairment (1,8,26,30,31,37). Periventricular white matter damage (PWMD) is a distinctive pathological feature of brain injury in septic neonates (38,63).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prevention of neonatal sepsis in infants born very preterm (<32 weeks' gestation) is clearly desirable as this would contribute to reducing mortality and morbidity (22,59). There is ample evidence indicating that neonatal sepsis can lead to long-term disability, including cerebral palsy, cognitive deficit, delayed mental and psychomotor, vision and hearing impairment (1,8,26,30,31,37). Periventricular white matter damage (PWMD) is a distinctive pathological feature of brain injury in septic neonates (38,63).…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal candidemia during the first week of life is less common and less well described than the later onset of this group of infections. According to Barton et al [33], risk factors for candidemia among neonates had not been studied before their research, in early onset disease (EOD, ≤7 days) or compared to late onset disease (LOD, >7 days). After a 2-year study, the authors concluded that risk factors such as birthweight <750 g, gestation <25 weeks, chorioamnionitis and vaginal delivery were strongly associated with EOD.…”
Section: Neonatal Candida Infectionsmentioning
confidence: 99%
“…Dissemination and cardiovascular involvement are common, and affected infants often die. Empiric treatment should be considered in these risk situations [33,34].…”
Section: Neonatal Candida Infectionsmentioning
confidence: 99%
“…Despite the high incidence of vulvovaginal candidiasis during pregnancy (13–20%) [ 1 , 2 ], Candida species rarely cause chorioamnionitis. A recent neonatal study demonstrated that chorioamnionitis is an important risk factor of invasive early-onset candidiasis in extremely low-birth-weight infants, which leads to high mortality (71%) and neurodevelopmental impairment rates (86%) [ 3 ]; thus, the establishment of antenatal management is crucial. Since the first case of chorioamnionitis caused by Candida albicans that resulted in preterm birth and neonatal death was reported in 1958 [ 4 ], many case reports and short case series have been published.…”
Section: Introductionmentioning
confidence: 99%